Calculation of the Neutrino Mass - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2020)
The determination of the neutrino mass is considered an important milestone in physics and especially in cosmology. Because it is so extraordinarily small, the usual methods for determining the mass of elementary particles fail. After Wolfgang Pauli's prediction of the neutrino in 1930, experimental proof was not possible until 1956, when an electron antineutrino met a proton and produced a positron and a neutron. The Karlsruhe Tritium Neutrino Experiment KATRIN [1.] is intended to determine the neutrino mass with unique accuracy or, if the sensitivity of the measuring technique is not yet sufficient, to further limit its upper limit. A theoretically exact determination of mass is not yet possible. The present publication is dedicated to this topic. Assuming a mass decay in the universe that includes the neutrino mass, a precise calculation method is proposed and subsequently justified. The effects of neutrino splitting from the proton are examined. In a cosmological perspective, further effects that neutrino decay could have on the expansion of space, gravity, dark mass, magnetic monopoles and time are investigated.